2014
DOI: 10.1186/1476-4598-13-216
|View full text |Cite
|
Sign up to set email alerts
|

Small nucleolar RNA 113–1 suppresses tumorigenesis in hepatocellular carcinoma

Abstract: BackgroundEmerging evidence suggests that small nucleolar RNAs (snoRNAs) are involved in tumorigenesis. The roles of small nucleolar RNA 113–1 (SNORD113-1) on the development of hepatocellular carcinoma (HCC) remain unknown.MethodsThe expression of SNORD113-1 was measured in 112 HCC tumor tissues using quantitative RT-PCR and compared with expression levels from with paired non-tumor tissues. The effects of SNORD113-1 on HCC tumorigenesis were investigated in HepG2 and Huh7 cells as well as a xenograft nude mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 46 publications
3
72
0
1
Order By: Relevance
“…snoRD113, snoRD114 and snoRD116, that belong to the C/D box class of snoRNAs were found to be remarkably downregulated in TNBC samples. The snoRNA113, which was significantly downregulated in TNBC samples has been previously reported to suppress tumorigenesis in hepatocellular carcinoma 76. While it was downregulated in our TNBC samples, snoRD114 was previously reported to be overexpressed in acute promyelocytic leukemia (APL) 77, suggesting, tissue specific action of this cluster of snoRNAs.…”
Section: Resultsmentioning
confidence: 51%
“…snoRD113, snoRD114 and snoRD116, that belong to the C/D box class of snoRNAs were found to be remarkably downregulated in TNBC samples. The snoRNA113, which was significantly downregulated in TNBC samples has been previously reported to suppress tumorigenesis in hepatocellular carcinoma 76. While it was downregulated in our TNBC samples, snoRD114 was previously reported to be overexpressed in acute promyelocytic leukemia (APL) 77, suggesting, tissue specific action of this cluster of snoRNAs.…”
Section: Resultsmentioning
confidence: 51%
“…Moreover, several studies showed that HSD17B13 expression was lower in HCC tumor tissue than in nontumor adjacent tissue . One study suggested that a low level of HDS17B13 mRNA in nontumor liver was associated with a higher rate of tumor recurrence after liver resection of HCC, but these results need external validation .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, small nucleolar RNAs (snoRNAs), which are non-coding RNAs that are 60-300 nucleotides in length, were proposed to be closely associated with various human diseases, including cancer (11,12). Several studies have reported that certain snoRNAs act as diagnostic or prognostic biomarkers and as therapeutic targets for HCC (13,14). Several in vitro and in vivo studies indicated that certain snoRNAs are involved in the regulation of the genesis and biological behavior of HCC, including cell proliferation, migration, apoptosis, cell cycle and metastasis.…”
Section: Introductionmentioning
confidence: 99%